The value of risk : Swiss Re and the history of reinsurance - Borscheid, Peter; Gugerli, David, 1961-; Straumann, Tobias (Oxford University Press, 2013)
This title explains how today's insurance industry developed and highlights the role of the reinsurance industry in spreading risks globally. It examines the development of insurance markets and of the reinsurance industry in particular, and the history of Swiss Re, one of the leading reinsurance companies in the world.